Imagineering “Green Civilization”:Critical Reflections on Eco-City Development in China - Neo, Choong Tiong Harvey (East Asian Institute, Singapore, 2014)
Workshop on “Towards a Livable and Sustainable Urban Environment: Eco-cities in East Asia”, East Asian Institute, Singapore, 27 Feb 2009